User experience evaluation of the Hurbanize app under nine sources of product emotion (Human Factors in Design, 2021)
Ideas to boost the redemocratization of urban spaces are urgent and essential. This study aims to evaluate user’s experiences with the app “Hurbanize: share ideas for the city”. The research presents four moments and separates thirty participants in three groups. Data collection uses Pick-A-Mood, explanation of emotions and user experience qualifications. Data analysis is done by arousal and valence model of mood, using appraisal theory and nine sources of product emotion. The results present increase in arousal and valence as well as perceptions of affinity, displeasure, credit, claim, apprehension and enjoyment towards the Hurbanize app.
Keywords: Urban renewal; User experience; Appraisal theory; Tactical urbanism